Variation in prostate cancer treatment and spending among Medicare shared savings program accountable care organizations. Issue 16 (15th June 2018) - Modi, Parth K.; Kaufman, Samuel R.; Borza, Tudor; Yan, Phyllis; Miller, David C.; Skolarus, Ted A.; Hollingsworth, John M.; Norton, Edward C.; Shahinian, Vahakn B.; Hollenbeck, Brent K.
Abstract : BACKGROUND: Accountable care organizations (ACOs) have been shown to reduce prostate cancer treatment among men unlikely to benefit because of competing risks (ie, potential overtreatment). This study assessed whether the level of engagement in ACOs by urologists affected rates of treatment, overtreatment, and spending. METHODS: A 20% sample of national Medicare data was used to identify men diagnosed with prostate cancer between 2012 and 2014. The extent of urologist engagement in an ACO, as measured by the proportion of patients in an ACO managed by an ACO‐participating urologist, served as the exposure. The use of treatment, potential overtreatment (ie, treatment in men with a ≥75% risk of 10‐year noncancer mortality), and average payments in the year after diagnosis for each ACO were modeled. RESULTS: Among 2822 men with newly diagnosed prostate cancer, the median rates of treatment and potential overtreatment by an ACO were 71.3% (range, 23.6%‐79.5%) and 53.6% (range, 12.4%‐76.9%), respectively. Average Medicare payments among ACOs in the year after diagnosis ranged from 16, 523.52 to 34, 766.33. Stronger urologist‐ACO engagement was not associated with treatment (odds ratio, 0.87; 95% confidence interval, 0.6‐1.2; P = .4) or spending (9.7% decrease in spending; P = .08). However, urologist engagement was associated with a lower likelihood of potential overtreatment (odds ratio, 0.29; 95% confidence interval, 0.1‐0.86; P = .03). CONCLUSIONS: ACOs vary widely in treatment, potential overtreatment, and spending for prostate cancer. ACOs with stronger urologist engagement are less likely to treat men with a high risk of noncancer mortality, and this suggests that organizations that better engage specialists may be able to improve the value of specialty care. Cancer 2018. © 2018 American Cancer Society . Abstract : Accountable care organizations vary considerably in terms of treatment, potential overtreatment, and spending for men with newly diagnosed prostate cancer. Those entities with strong urologist engagement are less likely to overtreat men unlikely to benefit, and this suggests that accountable care organizations that better involve specialists may be able to improve the value of some aspects of specialty care.